Impact of frailty on health-related quality of life 1 year after transcatheter aortic valve implantation. (18th May 2020) - Goudzwaard, Jeannette A; de Ronde-Tillmans, Marjo J A G; van Hoorn, Fleurance E D; Kwekkeboom, Eline H C; Lenzen, Mattie J; van Wiechen, Maarten P H; Ooms, Joris F W; Nuis, Rutger-Jan; Van Mieghem, Nicolas M; Daemen, Joost; de Jaegere, Peter P T; Mattace-Raso, Francesco U S
Abstract: Background: Transcatheter aortic valve implantation (TAVI) brings symptom relief and improvement in health-related quality of life (HRQoL) in the majority of patients treated for symptomatic, severe aortic stenosis. However, there is a substantial group of patients that do not benefit from TAVI. The aim of this study is to investigate the impact of frailty on HRQoL 1 year after TAVI. Methods: The TAVI Care & Cure Program is an ongoing, prospective, observational study including patients referred for TAVI to our institution. A comprehensive geriatric assessment was performed to evaluate existence of frailty using the Erasmus Frailty Score (EFS). HRQoL was assessed using the EQ-5D-5 L at baseline and 1 year after TAVI. Results: 239 patients underwent TAVI and completed HRQoL assessment 1 year after TAVI. Seventy (29.3%) patients were classified as frail (EFS ≥ 3). In non-frail patients, the EQ-5D-5 L index did not change (0.71(± 0.22) to 0.68(± 0.33) points, P = 0.22); in frail patients, the EQ-5D-5 L index decreased from 0.55(±0.26) to 0.44 points (±0.33) ( P = 0.022). Frailty was an independent predictor of deteriorated HRQoL 1 year after TAVI (OR 2.24, 95% CI 1.07–4.70, P = 0.003). In frail patients, the absence of peripheral artery disease (OR 0.17, 95% 0.05–0.50, P = 0.001) and renal dysfunction (OR 0.13, 95% CI 0.04–0.41, P = <0.001) at baseline was associated with improved HRQoL 1 year after TAVI. Conclusion: Frailty is associated with deterioration of HRQoL 1 year after TAVI. Notably, HRQoL did improve in frail patients with no peripheral arterial disease or renal impairment at baseline.